Violência x violência policial x capital social: estudo comparativo entre a cidade de Panambi e Itaqui-RS - Lucca, Humberto André Rodrigues (Pontifícia Universidade Católica do Rio Grande do Sul, 2016)
Made available in DSpace on 2016-06-02T12:45:15Z (GMT). No. of bitstreams: 1 000478689-Texto+Completo-0.pdf: 1712522 bytes, checksum: 456c6efb671c859f71b6148712088afc (MD5) Previous issue date: 2014 === This dissertation is a comparative study between the levels of social and police violence between the cities of Panambi and Itaqui in the State of Rio Grande do Sul in comparison with the levels of the social capital. In the last five years from 2008 to 2012, Itaqui presented a bigger percentage within 37% if taken into account crimes like: murders, robberies with killed victims, steals and drug's traffic. Distinction that also shows itself present in face of police violence indicators. The research studied the reasons that lead a town to present higher rates of violence than another, following similar surveys (because some places have high crime’s rates and others not?) Bailing to both other sciences such as sociology and political science (social capital) through the application of a field survey, detecting smaller social capital in Itaqui town that also proved more violent and more police violence, also with greater inequality by GINI index than Panambi. Therefore the first chapter presents the social, economic, cultural and historical aspects. The second chapter discusses violence (social and police) based on database from SSP - RS, and based on existing records in correctional section of the Corporation. The third chapter discusses the social capital (theoretics), and its relation to violence, as well as the parameters for the survey formatting applied. Finally, the fourth chapter deals with the outcome of the research with comparative analysis between the studied municipalities where depth is the theoretical basis of the object of study. The research allowed to consider social factors, social capital and inequality correlates with different levels of social violence and police detected in each municipality. Those policies geared solely to an increase of more police, more police cars, more repression show to be ineffective in the long term to reduce violence. === Esta dissertação trata de um estudo comparativo entre os níveis de violência da sociedade e policial entre os municípios de Panambi e Itaqui do Estado do Rio Grande do Sul, em cotejo com os níveis de capital social. No quinquídio de 2008 a 2012, Itaqui apresentou um percentual maior em 37% se levados em conta crimes como: homicídio, latrocínio, roubos, furtos e tráfico de drogas. Distinção que também se mostra presente quando aos indicadores de violência policial. A pesquisa estudou quais os motivos que levam um município apresentar índices de violência superiores aos do outro, seguindo pesquisas semelhantes (porque algumas localidades têm altas taxas de criminalidade e outras não?) socorrendo-se para tanto de outras ciências como a sociologia e a ciência política (capital social) por intermédio da aplicação de uma pesquisa de campo, sendo constatado um menor capital social em Itaqui, cidade que se mostrou também mais violenta e com maior violência policial, também com maior desigualdade pelo índice de GINI que Panambi. Para tanto o primeiro capítulo traz as características sociais, econômicas, culturais e aspectos históricos.O segundo capítulo aborda a violência (social e policial) com base no registro de dados da SSP – RS, e com base nos registros existentes na seção correcional da Corporação. O terceiro capítulo aborda o capital social, bases teóricas, e sua relação com a violência, bem como os parâmetros para formatação do survey aplicado. Por fim o quarto capítulo trata dos resultados da pesquisa com a respectiva análise comparativa entre os dois municípios estudados onde é aprofundado o aporte teórico sobre o objeto de estudo. A pesquisa permitiu ponderar que fatores sociais, capital social e desigualdade tem correlação com níveis diversos de violência social e policial detectados em cada município. Que as políticas voltadas unicamente ao incremento de mais policiais, mais viaturas, mais repressão mostram-se ineficazes a longo prazo para redução da violência.